Greenwitch - Cooper, Susan, 1935- (Cooper, Susan, 1935- Dark is rising sequence., 2000)
Jane's invitation to witness the making of the Greenwitch begins a series of sinister events in which she and her two brothers help the Old Ones recover the grail stolen by the Dark.